Graft-versus-host reaction manifested as toxic epidermal necrolysis in a patient with acute leukemia - Berkel, A. İzzet; Tınaztepe, Keriman (The Turkish Journal of Pediatrics, 1981)
A fatal graft-versus-host (g.v.h.) disease was observed in a 5-year-old male with acute leukemia who was treated with corticosteroids, purinethol and blood transfusions. A typical picture of toxic epidermal necrolysis showing intense erythema, bullous lesions and a positive Nikolsky’s sign was observed 7 weeks following the diagnosis of leukemia. The skin biopsy revealed acute epidermal necrolysis and focal single cell necrobiosis with intraepithelial lymphocytes, which is characteristic of g.v.h. reaction described mainly in patients after allogeneic bone marrow transplantation.
Keywords: acute leukemia; graft-versus-host reaction; toxic epidermal necrolysis